Craft and poverty alleviation in South Africa : an impact assessment of Phumani Paper : a multi-site craft-based poverty alleviation programme - Cohn, Taryn Claire (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MA)--University of Stellenbosch, 2004.